PERANCANGAN DAN VALIDASI ALAT PENGUKURAN KONSTANTA DISOSIASI ASAM PADA SUHU 30-70°C - Vitro Rahmat; Desi Kurniawan; Sholeh Maâ€™mun (Teknoin, 2016)
The greenhouse effect is caused by increasing emissions of greenhouse gases, e.g. carbon dioxide, in the atmosphere leading to the global warming problem. Thus necessary efforts to reduce the CO2 emissions are required, e.g. amine-based absorption method. Protonation constant is required for the VLE modeling needed in designing absorber and desorber column. For this purpose, an experimental setup was designed to measure alkanolamine protonation constants (pKa). However, the setup needs to be validated by measuring the protonation constants of acetic acid at a range of temperatures from 30 to 70°C. The validation results obtained were in good agreement with the literature data. For example, the pKa of the acetic acid at 30°C is 4.751 and this gives a deviation of 0.18% from the literature data.